Partisipasi Politik Masyarakat Tionghoa di Gang Pinggir dalam Pemilihan Kepala Daerah Dan Wakil Kepala Daerah Kota Semarang Tahun 2024 - Diva Ardyanasari; nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
Political participation is an essential element of democracy as it reflects citizens’ involvement in political and governmental processes. As an ethnic minority group in Indonesia, the Chinese Indonesian community has experienced unique historical dynamics in political life. Amid the broader democratic openness following the Reform Era, it is important to examine how this community participates in local political contests. This study aims to analyze the forms of political participation among the Chinese-Indonesian community in Gang Pinggir during the 2024 Semarang Regional Head Election and to identify the factors influencing such participation. This research employed a descriptive qualitative approach. Data were collected through interviews, documentation, and literature review. The informants consisted of members of the Chinese-Indonesian community in Gang Pinggir, the General Election Commission of Semarang City, and the Election Supervisory Agency of Semarang City. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that political participation among the Chinese-Indonesian community in Gang Pinggir is predominantly electoral, mainly through voting in the 2024 regional election. Participation in more active political activities such as campaigns, political organizations, and political mobilization remains relatively low. Based on Milbrath and Goel’s typology of political participation, the community is categorized as spectators. Factors influencing political participation include political awareness, access to political information, social environment, trust in election organizers, and rational considerations in determining political preferences. The study concludes that the political participation of the Chinese-Indonesian community in Gang Pinggir reflects involvement in local democracy, although it remains moderate and primarily oriented toward electoral activities.